Cost-variation analysis between different brands of cardiovascular drugs available in the Indian market - Reddy, P. Pavan Kumar; Devaraju, C.; Sathyanarayana, Chandana; Lakshmana, Megha M. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Cardiovascular diseases (CVDs) emerging as a leading cause of mortality in India, access to affordable medications is crucial for managing these conditions. Our study examined the significant cost variations among different brands of cardiovascular drugs available in the Indian market. The study was conducted to find out the cost variation in the cardiovascular drugs available in India and to evaluate the difference in cost of various brands of the same by calculating percentage of variation in cost. Methods: The analytical study was carried out by taking the cost of a particular drug in the same dosage forms and strength being manufactured by different companies was obtained from July-October 2024 edition of the current index of medical specialities (CIMS) and July-October 2024 edition of monthly index of medical specialties (MIMS) and percentage cost variation was calculated. Results: Our analysis revealed a wide price variation among various drug brands of cardiovascular drugs. Furosemide 40 mg tablet has shown the highest price variation (1572.86%), while least price variation is seen in hydrochlorothiazide 25 mg tablet (3.98%). Conclusions: Prices of various drugs used in the treatment of cardiovascular drugs show a wide variation in the Indian market. Medication adherence, community health, and the financial burden of healthcare costs on the country would all be improved by lowering price variation and making drugs more affordable. The findings highlight the urgency of implementing measures to reduce price variations and improve affordability, thereby enhancing healthcare access and mitigating the financial burden on individuals and society. However, it’s important to note the study’s limitations, including the selection of only a subset of drug brands available in CIMS and MIMS for analysis.